Bloodstream infections in patients with liver cirrhosis. Issue 3 (2nd April 2016) - Bartoletti, Michele; Giannella, Maddalena; Lewis, Russell Edward; Viale, Pierluigi
ABSTRACT: Bloodstream infections are a serious complication in patients with liver cirrhosis. Dysregulated intestinal bacterial translocation is the predominant pathophysiological mechanism of infections in this setting. For this reason enteric Gram-negative bacteria are commonly encountered as the first etiological cause of infection. However, through the years, the improvement in the management of cirrhosis, the recourse to invasive procedures and the global spread of multidrug resistant pathogens have importantly changed the current epidemiology. Bloodstream infections in cirrhotic patients are characterized by high mortality rate and complications including metastatic infections, infective endocarditis, and endotipsitis (or transjugular intrahepatic portosystemic shunt-related infection). For this reason early identification of patients at risk for mortality and appropriated therapeutic management is mandatory. Liver cirrhosis can significantly change the pharmacokinetic behavior of antimicrobials. In fact hypoproteinaemia, ascitis and third space expansion and impairment of renal function can be translated in an unpredictable drug exposure.